Proteome Analysis of Urinary Biomarkers in Acute Hypercoagulable State Rat Model - Jing, Jian; Du, Zhenhuan; Qin, Weiwei (Frontiers in Molecular Biosciences, 2021)
Thrombotic diseases are usually preceded by a hypercoagulable state in the body. This study aimed to screen potential urinary biomarkers for hypercoagulable state based on proteome analysis. Wistar rats were administrated with hemostatic agent etamsylate to establish hypercoagulable state. The urine samples were collected for proteome analysis. We found 20 proteins with levels more than 1.5 fold difference between control rats and model rats. We searched human homologs of 20 rat proteins and identified 15 human proteins. Of the 15 human homologous proteins, 9 were members of human Core Urinary Proteome. Human homologous proteins of differential proteins were highly expressed in 31 tissues in human, especially in the kidneys followed by digestive system and reproductive system. Surprisingly, we did not identify known coagulation factors as differential proteins in the urine of model rats. Hypercoagulable state of the body may not involve direct changes in coagulation factors, but causes the changes upstream of the coagulation cascade system. The common differential urinary proteins between different hypercoagulable states suggest some common pathways in the formation of hypercoagulable states, and may serve as potential biomarkers for the prevention and treatment of thrombotic diseases.